2023
DOI: 10.1101/2023.02.23.529717
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Chemogenetic activation of corticotropin-releasing factor-expressing neurons in the anterior bed nucleus of the stria terminalis reduces effortful motivation behaviors

Abstract: Corticotropin-releasing factor (CRF) in the anterior bed nucleus of the stria terminalis (aBNST) is associated with chronic stress and avoidance behavior. However, CRF+ BNST neurons project to reward- and motivation-related brain regions, suggesting a potential role in motivated behavior. We used chemogenetics to selectively activate CRF+ aBNST neurons in male and female CRF-ires-Cre mice during an effort-related choice task and a concurrent choice task. In both tasks, mice were given the option either to exer… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 71 publications
(151 reference statements)
1
0
0
Order By: Relevance
“…This would support research on the role of BNST in contextual fear memory (Goode et al, 2020; Hammack et al, 2015; Luyck et al, 2020; Sullivan et al, 2004; Urien & Bauer, 2022; Williams & Lattal, 2020; Williford et al, 2023). It would also support prior research demonstrating that BNST subdivisions and cell types may have specialized functions in behavioural output and threat processing (Bruzsik, Biro, Zelena, et al, 2021; de Araujo Salgado et al, 2023; Duque‐Wilckens et al, 2016; Giardino et al, 2018; Jaramillo et al, 2020; Jennings et al, 2013; Kim et al, 2013; Maita et al, 2023; Mazzone et al, 2018). Further research will be necessary to investigate the participation of BNST in hypothalamic regions in the regulation of defensive responses while foraging.…”
Section: Discussionsupporting
confidence: 78%
“…This would support research on the role of BNST in contextual fear memory (Goode et al, 2020; Hammack et al, 2015; Luyck et al, 2020; Sullivan et al, 2004; Urien & Bauer, 2022; Williams & Lattal, 2020; Williford et al, 2023). It would also support prior research demonstrating that BNST subdivisions and cell types may have specialized functions in behavioural output and threat processing (Bruzsik, Biro, Zelena, et al, 2021; de Araujo Salgado et al, 2023; Duque‐Wilckens et al, 2016; Giardino et al, 2018; Jaramillo et al, 2020; Jennings et al, 2013; Kim et al, 2013; Maita et al, 2023; Mazzone et al, 2018). Further research will be necessary to investigate the participation of BNST in hypothalamic regions in the regulation of defensive responses while foraging.…”
Section: Discussionsupporting
confidence: 78%
“…Previous research from our lab has shown that a chronic variable mild stress (CVMS) paradigm resulted in increased CRH signaling, increased miniature excitatory post-synaptic signaling, and suppressed M-current activity in the oval nucleus of the BNST in male mice (Hu, Liu et al, 2020). We have also recently demonstrated that chemogenetic activation of BNST CRH neurons reduced motivational behaviors as measured by effort-related choice in males and females (Maita et al, 2023). Studying the BNST neuronal populations involved in behaviors will be vital to elucidate the maladaptive effects of chronic stress.…”
Section: Introductionmentioning
confidence: 81%